The Effect of Multiple Intelligences-Based Learning Strategies on the Naturalist Intelligence of Elementary School Students - Mukhtar, Mukhtar; Kune, Syarifuddin; Syamsuddin, Rahmawati (Pedagogik Journal of Islamic Elementary School, 2022)
This study aims to determine the effect of multiple intelligences-based learning strategies on the natural intelligence of elementary school students on the concept of ecosystem. The subjects of this study were the fifth-grade students of Aroeppala State Elementary School, Makassar City, which consisted of 28 experimental class students and 25 control class students. This study uses a quantitative method with a quasi-experimental model with a non-equivalent control group design. The data collection technique is through observation, tests, and documentation. The data analysis technique used is descriptive and inferential analysis. The inferential test is in the form of an analysis prerequisite test consisting of a normality test and a homogeneity test as well as an N-Gain test, then a hypothesis test using a 2-sample T-test. The results showed an effect of multiple intelligences-based learning strategies on the natural intelligence of elementary school students. This strategy makes students actively involved in the teaching and learning process to provide a learning experience that is meaningful, more interesting, and easy to understand.